The Handbook of computational linguistics and natural language processing - Clark, Alexander ;Fox, Chris ;Lappin, Shalom (Somerset : Wiley-Blackwell, West Sussex, 2013)
This comprehensive reference work provides an overview of the concepts, methodologies, and applications in computational linguistics and natural language processing (NLP). Features contributions by the top researchers in the field, reflecting the work that is driving the discipline forward Includes an introduction to the major theoretical issues in these fields, as well as the central engineering applications that the work has produced Presents the major developments in an accessible way, explaining the close connection between scientific understanding of the computational proper.
Part I. Formal foundations -- Part II. Current Methods -- Part III. Domains of application -- Part IV. Applications.
Includes bibliographical references and index.
Keywords: COMPUTATIONAL LINGUISTICS